PENGARUH Aspergillus niger DAN PUPUK KANDANG AYAM BROILER TERHADAP KETERSEDIAAN DAN SERAPAN P SERTA PERTUMBUHAN JAGUNG PADA ANDISOL CANGAR - Dedi Darma Andrians; S Syekhfani; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Andisols have low phosporus availability because of amorphous (non-crystalline) of high allophane. This problem may be overcome by application of organic materials and utilization of phosphate solubilizing microbes such as Aspergillus niger. This fungi can facilitate phosphate bound Al and Fe to soluble and available to plants. The objective of this study were to explore the influence of Aspergillus niger and chicken broiler manure on the avaibility and P uptake by maize at grown on an Andisol. This study used a simple randomized design with six treatments, i.e. PK1 (control), PK2 (3.5 t ha-1 chicken broiler manure + 10 mL Aspergillus niger with the density is 109 propagul mL-1, PK3 (3.5 t ha-1 chicken broiler manure + 20 mL Aspergillus niger with the density is 109 propagul mL-1), PK4 (3.5 t ha-1 chicken broiler manure + 30 mL Aspergillus niger with the density is 109 propagul mL-1), PK5 (3.5 t ha-1 chicken broiler manure + 40 mL Aspergillus niger with the density is 109 propagul mL-1), PK6 (3.5 t ha-1 chicken broiler manure + 50 mL Aspergillus niger with the density is 109 propagul mL-1), with three replicates. Results of this study showed that chicken broiler manure and Aspergillus niger could increase P-availability and P-uptake by maize in an Andisol. The most effectives dose of Aspergillus niger was 50 mL with density 109 propagul mL-1..